2004
DOI: 10.1086/379857
|View full text |Cite
|
Sign up to set email alerts
|

ChandraandXMM-NewtonObservations of RDCS 1252.9-2927, A Massive Cluster atz=1.24

Abstract: We present deep Chandra and XMM-Newton observations of the galaxy cluster RDCS 1252.9À2927, which was selected from the ROSAT Deep Cluster Survey (RDCS) and confirmed by extensive spectroscopy with the Very Large Telescope at redshift z = 1.237. With the Chandra data, the X-ray emission from the intracluster medium is well resolved and traced out to 500 kpc, thus allowing a measurement of the physical properties of the gas with unprecedented accuracy at this redshift. We detect a clear 6.7 keV iron K line in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 35 publications
(42 reference statements)
6
125
0
Order By: Relevance
“…Our analysis supports the evidence of a constant C-M slope up to z = 1, meaning a correspondingly constant mass-metallicity relation. We stress that most of the highest redshift clusters detected so far were selected in the X-ray band, in particular those at z = 1.24 (Blakeslee et al 2003;Rosati et al 2004) and z = 1.4 (Mullis et al 2005). However, both these clusters have a velocity dispersion of about 800 km s −1 and intracluster gas temperature kT ∼ 6 keV, typical of rich clusters (Bahcall 1988;Arnaud et al 2005).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our analysis supports the evidence of a constant C-M slope up to z = 1, meaning a correspondingly constant mass-metallicity relation. We stress that most of the highest redshift clusters detected so far were selected in the X-ray band, in particular those at z = 1.24 (Blakeslee et al 2003;Rosati et al 2004) and z = 1.4 (Mullis et al 2005). However, both these clusters have a velocity dispersion of about 800 km s −1 and intracluster gas temperature kT ∼ 6 keV, typical of rich clusters (Bahcall 1988;Arnaud et al 2005).…”
Section: Discussionmentioning
confidence: 85%
“…However, both these clusters have a velocity dispersion of about 800 km s −1 and intracluster gas temperature kT ∼ 6 keV, typical of rich clusters (Bahcall 1988;Arnaud et al 2005). The X-ray luminosities of these two clusters in the 0.5-2 keV band are 1.9 × 10 44 and 3.0 × 10 44 erg s −1 h −2 70 respectively (Rosati et al 2004;Mullis et al 2005), again typical of clusters with richness class greater than 2 (Ledlow et al 2003). Rich clusters of these redshifts are just at the limit of our present (2+1)D analysis based on photometric observations.…”
Section: Discussionmentioning
confidence: 95%
“…If cluster masses have grown by a factor 2 or 3 since z ≃ 1, as some authors suggest 33 In order to compare our data with simulations we use the bolometric X-ray luminosity of each system (L X ) 11,12,34,35 as this can be used to determine cluster mass from power-law scaling relations 36,37 . For J2235 we use the published X-ray luminosity 15 …”
Section: Cluster Massesmentioning
confidence: 99%
“…However, significant progress is still required to fully characterize the high redshift (z > ∼ 0.9) cluster population, which has been limited to few known and well studied test objects so far (e.g., Rosati et al 2004;Hashimoto et al 2005). Detailed studies have recently revealed large-scale structure (LSS) associated with several of the known bona fide X-ray clusters in the Lynx field at z = 1.27 (Nakata et al 2005) and for RDCS J1252.9-2927 at z = 1.24 (Tanaka et al 2007).…”
Section: Introductionmentioning
confidence: 99%